2021
DOI: 10.3928/19382359-20211111-01
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Fecal Microbiota Transplantation in Recurrent Clostridioides Difficile

Abstract: With the rising rates of Clostridioides (Clostridium) difficile infection (CDI) in children, recognizing the limitations of CDI-directed antibiotic therapy, especially in recurrent CDI (rCDI), is important. Fecal microbiota transplantation (FMT), which directly targets the underlying gut dysbiosis present in rCDI, is an important treatment option to consider in rCDI. This article will summarize indications, procedures, effectiveness, and the safety of FMT for rCDI in pediatric patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Here an entire community of bacteria and viruses, including metabolites and other fecal particles, are transferred from a healthy donor to a patient to stabilize the GM community. This is used to treat recurrent Clostridioides di cile infection (rCDI) in adults and children with very high cure rates [24,25]. Recently, a small trial investigated maternal FMT in seven cesarean-born babies and found no adverse effects and an infant GM closer resembling infants born vaginally [26].…”
Section: Introductionmentioning
confidence: 99%
“…Here an entire community of bacteria and viruses, including metabolites and other fecal particles, are transferred from a healthy donor to a patient to stabilize the GM community. This is used to treat recurrent Clostridioides di cile infection (rCDI) in adults and children with very high cure rates [24,25]. Recently, a small trial investigated maternal FMT in seven cesarean-born babies and found no adverse effects and an infant GM closer resembling infants born vaginally [26].…”
Section: Introductionmentioning
confidence: 99%